The Economic Effects of Counterfeiting and Piracy : A Review and Implications for Developing Countries - Fink, Carsten; Maskus, Keith E.; Qian, Yi (World Bank, Washington, DC, 2016)
Policy makers around the world recognize the potentially harmful consequences of trademark counterfeiting and copyright piracy. Indeed, many countries have recently initiated policy reforms to strengthen the enforcement of intellectual property rights (IPR). Further, minimum standards of enforcement have been incorporated in many international treaties, especially trade agreements. This emphasis on enforcement raises basic questions about the actual impacts of IP rights infringement, which differ across the types of IPR and economic sectors. The authors review the academic literature and other studies in the public domain to evaluate what has been learned about these socioeconomic effects, with an emphasis on developing countries where possible. They also identify important gaps in our understanding of the consequences of counterfeiting and piracy and develop recommendations on how governments might collect data and conduct studies to better inform IPR enforcement policy.